Evaluation of Daytime Sleepiness and Academic Performance in Dentistry Students - Pierri, Ricardo Augusto Gonçalves [UNESP] (2021)
Objective This study aimed to evaluate the daytime sleepiness and sleep quality of students in different academic years of the dental school program. Materials and Methods A total of 221 students, from the 1st to the 5th year, answered the questionnaires: Epworth, Pittsburg, Nasal Obstruction Symptom Evaluation, and Berlin, related to daytime sleepiness, sleep quality, nasal obstruction, and obstructive sleep apnea syndrome (OSAS), respectively. Statistical Analysis The Kolmogorov-Smirnov test was used to assess the normality of continuous quantitative data and, posteriorly, the chi-square test was used to show if there were any associations. The significance level adopted was 5%. Results An association between daytime sleepiness and nasal obstruction was observed at the beginning of the school year (T1) (p = 0.002) and at the end of the school year (T2) (p = 0.043). In T2, an association between nasal obstruction and sleep quality was also observed (p = 0.026). The academic performance (AP) was only associated with the OSAS in T1 (p = 0.012). There was no significant difference in AP between the beginning and the end of the academic year (p = 0.935). Conclusion With the methodology used, it was observed that nasal obstruction influenced sleep quality and daytime sleepiness, and daytime sleepiness did not have any influence on AP.